FUNGSI ASOSIASI PORNOGRAFI DALAM WACANA HUMOR - YUNIAWAN, TOMMI (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2007)
Abstract This research is aimed at describing pornographic associative meaning function in humor texts. The data ot this research are humor texts written in Indonesian which have pornographic association as well as their contexts. Those data are obtained from humor texts. The texts are selected in a random way by taking into account the following considerations: (1) those texts are in the Indonesian language, (2) those texts depict the current use of language, and (3) those texts contain pornographic associative meaning. The data are collected from Humor collection. These data are gathered by taking some notes from or by recording humor texts containing pornographic associative meaning and the contexts on data cards or corpus data. Data analysis in this very research is carried out through two procedures: (1) analysis during data collection procces, and (2) analysis after data collection. Afterwards, in order to reach a precise interpretation of the result in the research, there are some steps taken: (1) discussion, (2) rechecking, and (3) consultation. Based on the data analysis discussion result, several points can be drawn as the conclusions as regard to the pornographic association functions in humor texts including: demanding attention, entertaining, evoking curiosity, euphemism, and deceiving readers.